The Technique of Bebano Drums on Accompanying Jogi Dance in Wansendari Art Studio Batam City - Rhema Faith; Panji Suroso (Universitas Negeri Medan, 2021)
The purpose of this study is: To find out how the technique of playing Gendang Bebano in accompanying the jogi dance in the wansendari art studio. The approach and type of research used by the researcher is descriptive qualitative. This research was conducted at the Wansendari Art Studio, Batam City, so the population of this study were all members of the Wansendari Art Studio. While the samples of this study were members of the studio musicians, the head of the studio, the instructor of the studio as well as the head of culture in the city of Batam. The writing uses data collection techniques in the form of: observation to produce valid data regarding the technique of playing the Gendang Bebano in accompanying the jogi dance. Interview to get the results of research on the technique of playing Gendang Bebano in accompanying the jogi dance. Documentation for additional data in the form of photos, recordings and videos. The results of this study prove that the technique of playing the Gendang Bebano in the form of the body position of the drummers is sitting cross-legged and the drums are above the players' feet The Bebano of the drum is held by both players' hands and produces the sound of tak, pung, plang, tung. On the sound without using the index finger, middle finger, third finger, and little fingers, they are hit on the edge of the drum skin. The sound of pung uses the index finger, middle finger, third finger, and little finger but is hit in the middle area of the drum with the fingers in a straight position with the palm of the hand attached to the edge of the drum. In the plaang sound, the middle finger, third finger, and little finger are beaten on the edge of the drum but the palms are attached to the circumference of the drum. For the tung sound, use 4 straight fingers and hit in the middle of the drum.